A Cross-Sectional Study Identifying Medication Adherence Technologies (MATech) in Sweden Using Behavior Change Techniques - Ekenberg M; Landin F; Wettermark B (Patient Preference and Adherence, 2024)
Marie Ekenberg, Fanny Landin, Björn Wettermark Department of Pharmacy, Uppsala University, Uppsala, SwedenCorrespondence: Marie Ekenberg, Department of Pharmacy, Uppsala University, Box 580, Uppsala, 751 23, Sweden, Email marie.ekenberg@farmaci.uu.seBackground: Poor medication adherence is a well-recognized problem, and behavior change techniques (BCTs) have shown promise in improving patient adherence to prescribed drug treatment. Through the utilization of medication adherence technologies (MATech), these BCT interventions could be delivered effectively in a person-centered way. MATech can be defined as systems, services or physical devices (hardware), with a digital component, used to support patients in their drug utilization. However, there is a lack of knowledge regarding their availability and to what extent they apply evidence-based BCTs.Purpose: This study aimed to identify and describe MATech with BCT interventions available in the Swedish language.Methods: A cross-sectional survey study was conducted in 2023. After identifying potential MATech developers by contacting umbrella organizations in the private sector, public agencies and regions, and conducting an app search, a survey was distributed to 381 potential MATech developers. Included MATech were in Swedish, used by patients, incorporated a BCT intervention, and had survey response from the developer. The survey was based on the BCT taxonomy and the framework of attributes from the COST ENABLE project, and included questions regarding BCT features. Following correspondence with 189 potential developers, 32 with products of interest responded to the survey, and 21 MATech were identified (12 standalone software and nine hardware solutions).Results: Among the 21 MATech identified, nine were hardware and ten were specifically designed for a particular disease or medication. The majority of technologies incorporated BCTs of reminding the patient to take the medication (81%), information about the treatment (71%) and providing feedback on the monitoring of medication adherence or clinical outcomes (76%).Conclusion: Swedish-language MATech employing BCTs are available, encompassing both hardware and software solutions. There is a need to enhance the visibility of these technologies, enabling patients to discover and utilize the support they provide.Keywords: persistence, telemedicine, eHealth, mHealth, behavior intervention, adherence